Effect of Liquidity and Dividend Pay-out on Financial Performance of Deposit Taking SACCOs in Kenya - Robert Lukhanda Shibutse; Elizabeth Kalunda; George Achoki (Integrated Journal of Business and Economics (IJBE), 2019)
Capital structure is one of the fundamental aspects to the success of Deposit Taking Savings (DPS) and Credit Cooperative Societies (CCS) as it influences the realization of its objectives and goals. The study intended to determine the effect of two capital structure determinants; liquidity and dividend payout, on financial performance as measured by Return on Assets of DPS and CCS, in Kenya. The study was grounded on the Pecking order and  Free cash flow capital structure theories. The study utilized a mixed research design using primary and secondary data for the period 2013 to 2017. The population of the study was 174 DPS and CCS. Stratified and purposive sampling technique was employed. Descriptive statistics and a regression model were used to analyze the data. Results revealed that liquidity and dividend pay-out had a significant and positive effect on the financial performance of DPS and CCS in Kenya. The study concluded that liquidity and dividend pay-out play a significant role in the financial performance of DPS and CCS. The study recommends having in place an Assets and Liabilities  Committee in each DPS and CCS that would help manage the assets and liabilities of the institution, ensuring adequate liquidity and cash flow management. Having in place a robust dividend policy that addresses; the basis of the rate of payments and activities that would require funding of which internally generated funds by way of dividend retention, is also critical.